Study protocol. The Childhood Health, Activity, and Motor Performance School Study Denmark (The CHAMPS-study DK) - Wedderkopp Niels; Jespersen Eva; Franz Claudia; Klakk Heidi; Heidemann Malene; Christiansen Christina; Møller Niels; Leboeuf-Yde Charlotte (BMC, 2012)
Abstract Background An increasingly passive life-style in the Western World has led to a rise in life-style related disorders. This is a major concern for all segments of society. The county council of the municipality of Svendborg in Denmark, created six Sport Schools with increased levels of suitable physical activities, which made it possible to study the health outcomes in these children whilst comparing them to children who attended the 'normal' schools of the region using the design of a "natural experiment". Methods Children from the age of 6 till the age of 10, who accepted to be included in the monitoring process, were surveyed at baseline with questionnaires, physical examinations and physical and biological testing, including DXA scans. The physical examination and testing was repeated during the early stage of the study. Every week over the whole study period, the children will be followed with an automated mobile phone text message (SMS-Track) asking questions on their leisure time sports activities and the presence of any musculoskeletal problems. Children who report any such problems are monitored individually by health care personnel. Data are collected on demography, health habits and attitudes, physical characteristics, physical activity using accelerometers, motor performance, fitness, bone health, life-style disorders, injuries and musculoskeletal problems. Data collection will continue at least once a year until the children reach grade 9. Discussion This project is embedded in a local community, which set up the intervention (The Sport Schools) and thereafter invited researchers to provide documentation and evaluation. Sport schools are well matched with the 'normal' schools, making comparisons between these suitable. However, subgroups that would be specifically targeted in lifestyle intervention studies (such as the definitely obese) could be relatively small. Therefore, results specific to minority groups may be diluted. Nonetheless, the many rigorously collected data will make it possible to study, for example, the general effect that different levels of physical activity may have on various health conditions and on proxy measures of life-style conditions. Specifically, it will help answer the question on whether increased physical activity in school has a positive effect on health in children.